Tren Penggunaan Key Opinion Leaders Sebagai Media Komunikasi Pemasaran dalam Bidang Kecantikan - Aurelia Ayudila Ageng; Chintia Marcelly Nabela; J. A. Wempi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
This study focuses on the use of Key Opinion Leaders (KOL) as a marketing communication strategy in the beauty industry. The aim is to understand the role of KOL in increasing brand awareness, building consumer trust, and driving purchasing decisions. This study uses qualitative methods with interviews and literature studies to explore the experiences of several beauty brands in Indonesia such as Rayya Beauty, Glowsicha, and Grace and Glow. The results show that KOLs are effective in conveying brand messages authentically through creative content such as product reviews. Selecting KOLs that are in line with brand values and audiences is the key to success. Conclusion of this study is KOLs play an important role in supporting digital marketing despite challenges such as changes in social media trends.